Persepsi Gender dan Relasi Sosial Di Masyarakat - Zulyadain Zulyadain (LPPM IAIN Sorong, 2017)
When the woman came out of the house, she should cover all of her body and hands from the view of other men. Not only that, they should disguise themselves from the attention of people who might know him. If a friend visiting her husband, while her husband was not at home, she should not have to ask at length to his guests. It intends to maintain her honor and dignity of her husband. As expressed by Imam Ghazali, he gives testament kindness to women, because they (the women) are like prisoners for you. Surely you do not have any rights from them except goodness; unless they (women) do bad deeds are obvious (against). If the woman’s misconduct, then she separated with bed, and beat with a gathering that did not hurt. If she was to obey you, do not you looking for another reason to disturb him. Remember, you actually have the right to your wife, and your wife has a right over you. Among your rights on your wife is a mat wife forbid you to people you do not like and your wives shall not allow the entry of people you do not like. Remember, that among your wife right over you are getting clothes and a decent living. Religious classical views are discussed in this paper.